Psoas muscle metastasis in cervical cancer: A case study and literature review - Jain, Himanshi Avinash; Kumar Bagri, Puneet; Tripathy, Amruta; Chaudhary, Kiran G.; Joshi, Hetal (Indian Journal of Case Reports, 2024)
Cervical cancer is the second most common cancer in India. Despite having long disease-free survival post-treatment, patients do present with local recurrence or distant metastasis post-treatment. The usual sites of metastasis are lymph nodes, lung, bone, liver, and peritoneum. Skeletal muscle metastasis in a known case of carcinoma cervix is a rare entity. Less than 1% of cases have skeletal muscle metastasis and the differential diagnoses include sarcoma, hematoma, and abscess. Among the patients with skeletal metastasis, psoas muscle involvement is more common. Here, we report the case of a 60-year-old female who was diagnosed with carcinoma cervix FIGO stage IIIc1 based on clinical, radiological, and pathological findings. Post-radiation treatment (External Radiation with concurrent chemotherapy followed by Brachytherapy), the patient was on follow-up and then after 1 year presented with left lower backache. On positron emission tomography-computed tomography, a malignant mass was seen involving the left psoas major muscle. Pathological examination showed metastatic squamous cell carcinoma with a known primary in the cervix. She is now on Palliative Chemotherapy.